Records as strategic resource in the Malaysian public sector / Mohammad Azhan Abdul Aziz ... [et al.] - Abdul Aziz, Mohammad Azhan; Hussin, Norhayati; Abdul Rahman, Abd Latif; Mohamad Rosman, Mohamad Rahimi; Ab. Ghani, Nor Alina (Universiti Teknologi MARA, Perlis, 2024)
Records may be used to ensure transparency, to keep individuals and organisations responsible for their acts and responsibilities, and to show that organisations have met legal or regulatory standards or accepted best practices. Records appear as a medium to improve the effectiveness and efficiency of the organisation, it becomes a strategic resource that provides information for future use. This study aims to describe how public records are managed and used among officers in departments and ministries of the Malaysian government. The respondents and key informants engaged in this study are Diplomatic Administer Officers (PTD) from different position grades starting from grade M44 to JUSA because they are categorized as top management that acts as administer, policymaker, decision-maker, etc. in the organisation. The respondents were randomly selected from twelve ministries and one department of the Malaysian public sector in Putrajaya. The study conducted is quantitative method. Findings show that all hypotheses are accepted. Records users were found to have a significant and positive relationship with the strategic use of records. Records value was also found to have a significant and positive relationship with strategic use of records same as the relationship between records user and records value. Moreover, the records’ value is hypothesized as a mediator between the records user and strategic use of records also indicates the same result. The results of the study have contributed to the development of a research model and theory for using records as a strategic resource, especially, in the government sector. Government servants especially PTD must use records as one of the strategic resources in carrying out their daily affairs.